BIOTA OF SAGARTAL GWALIOR, MADHYA PRADESH, AS A RESULT OF MANY CONTAMINANTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2019)
The current research was carried out at Sagartal located in Gwalior city, Madhya Pradesh. It is a 0.48 km2 deep water pool established for municipal water supply during Tomar Dynasty in 15th Century. This urban pool is encircled by concrete walls and there is supply of surface runoffs during monsoonal season to fill it up. Basically, a rainwater-fed pool, it is a source of perpetual supply of water to the urban population of Gwalior City for different uses from historical period. However, infiltration of residential sewage and immersion of idols during festival seasons has brought significant contamination to this water body. Once flourishing with fishes and water fowl the urban pond is now clutching to life owing to degradative human activity. The current research hence, was carried up to evaluate the physicchemical state of Sagartal and consequences of its pollutants on the biota present.